Serum carcinoembryonic antigen and carbohydrate antigen 19-9 as preoperative diagnostic biomarkers of extrahepatic bile duct cancer. Issue 6 (22nd December 2021) - Kim, Hyeong Seok; Han, Youngmin; Kang, Jae Seung; Kang, Yoon Hyung; Lee, Mirang; Sohn, Hee Ju; Kim, Hongbeom; Kwon, Wooil; Jang, Jin-Young
Abstract: Background: Serum carcinoembryonic antigen (CEA) and carbohydrate antigen (CA) 19-9 have been proposed as useful preoperative biomarkers of extrahepatic bile duct cancer (EBDC). This study investigated the accuracy of CEA and CA19-9 for preoperative diagnosis of EBDC. Methods: Patients who underwent surgery for EBDC at a tertiary centre between 1995 and 2018 were studied, and those with concurrent hepatobiliary diseases (including gallbladder cancer, intraductal papillary mucinous neoplasms of pancreas), which could affect CEA or CA19-9 levels, were excluded. The control group included patients who underwent cholecystectomy for benign gallbladder diseases during the same period. Diagnostic accuracy was determined using sensitivity, specificity and area under the receiver operating characteristic curve (AUC). Results: After excluding 23 patients, 687 patients (488 men and 199 women, mean age 65.8 years) were compared with the control group of 2310 patients. Median CEA and CA19-9 levels were 1.8 μg/l and 47.0 kU/l in patients with EBDC. CEA (cut-off 5.0 μg/l) showed AUC of 0.541, sensitivity 9.0 per cent and specificity 99.2 per cent, whereas CA19-9 (cut-off 37.0 kU/l) showed AUC of 0.753, sensitivity 56.2 per cent and specificity 94.5 per cent. Sensitivity of CA19-9 was lower in early (T stages 0–II) than advanced (T stages III and IV) cancer (47.0 versus 64.9 per cent), and also lower in N0 stage cancer than lymph node metastasis (50.1 versus 68.8 per cent). Conclusion: Serum CEA and CA19-9 showed low sensitivity limiting their usefulness as diagnostic biomarkers of EBDC. Abstract : To investigate the diagnostic accuracy of serum carcinoembryonic antigen (CEA) and carbohydrate antigen (CA) 19-9, the authors analysed 710 patients for extrahepatic bile duct cancer. CEA showed relatively low, but CA 19-9 showed moderate sensitivity for the diagnosis; sensitivity was lower in early T stage and N0 cancer.